KEPEMIMPINAN SITUASIONAL DAN KOMUNIKASI INTERPERSONAL DALAM MENINGKATKAN KOMITMEN GURU - Heni Hikmayani Fauzia; Bibin Rubini; Widodo Sunaryo (JURNAL MANAJEMEN PENDIDIKAN, 2018)
This research outlines the correlation between the headmasters situational leadership and interpersonal communication on organizational commitment. The research was conducted in private islamic school in the Sagaranten Sukabumi, West Java,Indonesia. Survey and data were conducted by applying regression and correlation analysis to test the correlation of two independent variables of situational leadership and interpersonal communication to one independent variable of organizational commitment. Tested on the level of confident of 0,05 and 0,01 to 109 teachers by using proportional random sampling, the result reveals that situational leadership can improve organizational commitment up to 18,75%, interpersonal communication contributes 10,47%. It can be inferred that organizational commitment can be enhanced through situational leadership and interpersonal communication.Keywords : Situasional Leadership, Interpersonal Communication , Organizational Commitment